ASSESSMENT OF RURAL FARMERS’ PERCEIVED EFFECT OF SOIL EROSION ON FARMING ACTIVITIES IN IKEDURU LOCAL GOVERNMENT AREA OF IMO STATE, NIGERIA - Ominikari, Abraham Godwin; Nimiye, C. Morgan (FUDMA JOURNAL OF SCIENCES, 2023)
The study assessed rural farmers’ perceived effect of soil erosion on farming activities in Ikeduru local government area of Imo State, Nigeria. Multi-stage sampling technique was used to select 120 rural farmers. Data collection was through structured questionnaire and analyzed using descriptive statistics such as mean and percentage. Findings reveal that excessive rainfall (= 4.13), lack of good drainage system (= 3.95), large scale cutting of forest (= 3.75), deforestation (= 3.68) among others were the mean responses of farmers on the perceived causes of soil erosion. The study also revealed that ditches made by soil erosion in the area is so deep and horrifying (= 3.97), the level of erosion in the area has gone beyond individual control (= 3.78) and the level of soil erosion in the area is high (= 3.65) were the mean responses of farmers on level of soil erosion. Furthermore, land degradation (= 3.93), reduced crop yields (= 3.85), low food production (= 3.85), general decrease in soil fertility (= 3.80) among others were perceived effects of soil erosion on farming activities. From the findings, it was concluded that there were perceived negative effects of soil erosion on farming activities. The study recommended that government should provide assistance in the areas of repairs of existing erosion sites, establishment of soil erosion research centers, and provision of proper climate data especially on rainfall and forest regeneration to help reduce and control the perceived negative effects of soil erosion on farming activities in the study area.